Prevalence of sexual coercion and its association with unwanted pregnancies among young pregnant females in Kampala, Uganda: a facility based cross-sectional study - Tusiime, Suzan; Musinguzi, Geofrey; Tinkitina, Benjamin; Mwebaza, Norah; Kisa, Rose; Anguzu, Ronald; Kiwanuka, Noah (BMC women's health, 2015)
Sexual coercion is associated with sexually transmitted infections and unwanted pregnancies with consequential unsafe abortions and increased maternal morbidity and mortality. Current literature focuses mainly on its risk factors but less on its resultant deleterious health effects. We conducted a study to determine the prevalence of sexual coercion and its association with unwanted pregnancies among young pregnant women. In a cross-sectional study, four hundred and sixteen (416) consenting pregnant females aged 15–24 years attending antenatal clinics in Lubaga division Kampala district in Uganda were enrolled using systematic sampling. Quantitative and qualitative data on sexual coercion were collected by female interviewers. Adjusted Prevalence Proportion Ratios (Adj. PPRs) of unwanted pregnancy and associated 95 % confidence intervals were estimated by generalized linear models with log link function and Poisson family distribution using robust variance estimator. Quantitative data were analyzed using Stata version 10.0, while qualitative data were analyzed using manifest content analysis. Prevalence of sexual coercion was 24 % and was higher among those who had non consensual sexual debut (29.0 %) compared with those who had consensual sexual debut (22.6 %). The prevalence of unwanted pregnancy was 18.3 % and was higher among participants who had been sexually coerced relative to their counterparts (p < 0.001). History of sexual coercion in the past 12 months and non consensual sexual debut were associated with unwanted pregnancy [adj.PPR = 2.23, 95 % CI: (1.49-3.32)] and 1.72, 95 % CI: (1.16- 2.54)] respectively. Qualitative results indicated that different forms/contexts of sexual coercion, such as deception, transactional sex and physical force influenced unwanted pregnancies. This study highlights that a quarter of our participants in our quantitative study had experienced sexual coercion in the past twelve months and nearly a third of these, had history of non consensual sexual debut. Unwanted pregnancy was higher among the sexually coerced and those who had non consensual sexual debut. Sexual coercion among pregnant women aged 15–24 years in Kampala, Uganda is high and is significantly associated with unwanted pregnancy. Comprehensive sex education targeting young people (<25 years), along with availability and access to youth friendly centers may be useful in addressing sexual coercion and its negative outcomes.
Keywords: Young women; Sexual coercion; Unwanted pregnancy